VD_FINDINFO Arrêt / 2024 / 580 vom 20. Juni 2024 - VD Tribunal cantonal (2024)
PRIME D'ASSURANCE-MALADIE, CHANGEMENT DE CAISSE, REJET DE LA DEMANDE, DETTE DE COTISATION | 64a al. 1 LAMal, 64a al. 6 LAMal, 105l OAMal